The next generation of triglyceride-lowering drugs: will reducing apolipoprotein C-III or angiopoietin like protein 3 reduce cardiovascular disease?. Issue 3 (June 2020) - Reeskamp, Laurens F.; Tromp, Tycho R.; Stroes, Erik S.G.
Abstract : Purpose of review: Apolipoprotein C-III (ApoC-III) and angiopoietin like protein 3 (angptl3) have emerged as key regulators of triglyceride metabolism. Based on Mendelian randomisation studies, novel therapeutic strategies inhibiting these proteins using monoclonal antibodies or gene silencing techniques might reduce residual cardiovascular disease (CVD) risk in dyslipidemic patients. This article aims to review the role of apoC-III and angptl3 in triglyceride metabolism and combine early clinical evidence of CVD reducing potential of these new therapeutic targets. Recent findings: Angptl3 inhibition by mAb or antisense therapy has recently completed phase I and II studies, respectively and demonstrate robust apolipoprotein B (apoB) lowering up to 46%. Volanesorsen is an antisense therapy approved for patients with extremely elevated plasma triglyceride levels in which it showed no consistent apoB reduction. However, the GalNAc-conjugated oligonucleotide showed moderate (up to ∼30%) apoB reduction in a phase 1/2a dose-finding study. Summary: Angptl3 and apoC-III are novel targets in lipoprotein metabolism that reduce triglycerides when inhibited. The expected CVD risk reduction may be mediated through reduced triglyceride-rich lipoprotein particle number, reflected by apoB, rather than triglyceride reduction per se. Limited human evidence shows that apoC-III and angptl3 inhibition both potently lower triglycerides, but since angptl3 inhibition reduces apoB more robustly it may be expected to confer more favorable CVD risk reduction.